Pemanfaatan Teknologi Budikdamber (Budidaya Ikan di dalam Ember) Sebagai Model Urban Farming Berkelanjutan - Muhammad Marzuki; Bagus Dwi Hari Setyono; Laily Fitriani Mulyani; Andre Rachmat Scabra (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Fish is a food of high quality and is very beneficial for the health of the body. The various benefits of fish meat will only be obtained if the fish consumed is fresh. In conditions that are not fresh (rotten), the nutritional content in fish meat is damaged. One of the efforts that can be done so that the consumption of fresh fish can be carried out continuously is to carry out urban farming activities, namely the cultivation of fish in buckets (budikdamber). This community service activity aims to increase knowledge and provide technical guidance to partners involved in the application of bucket fish cultivation technology. This community service activity is carried out through various methods of structured activities, namely site surveys, preparation of socialization materials and technical guidance for activities, formation of technology models, technical implementation assistance, and evaluation. The activity was carried out in "Jangkar Ampenan" youth group located in Tangsi neighborhood, South Ampenan District, Mataram City. The materials presented during the activity included preparation (tools, materials, work methods), technical assembly of fish farming equipment, feeding management, water quality management, and harvest management. The tools and materials needed in this activity include a 150 liter capacity bucket, catfish measuring 5-7 g/head, commercial catfish feed, kale seedlings, pipes, wire, 200 ml plastic cups, drill and grinder, seser, and aerator. . Based on the activities that have been carried out, the conclusion of this community service activity is that information, knowledge, and technical guidance have been conveyed to partners about fish farming technology in buckets (budikdamber).